Occupational risk of bloodborne infections among healthcare workers and strategies for their risk management - T. S. Yuzhanina; V. A. Kukarkina; A. A. Golubkova; A. S. Podymova (Фундаментальная и клиническая медицина)
Aim. To identify occupational risks of bloodborne infections among healthcare workers in order to develop effective risk management strategies. Materials and methods. Investigation reports and incident records were analyzed for 3,256 occupational exposure events involving healthcare workers in Sverdlovsk Region from 2013 to 2023. Results. From 2013 to 2023, the incidence rate of blood exposure incidents among healthcare workers was 6.6 per 1,000 (95% CI: 6.1– 7.1). The risk varied depending on the type of medical department, the nature of medical procedures, job role, length of professional experience, day of the week, and time of day. The highest risk of occupational infection was observed among surgeons, traumatologists, obstetrician-gynecologists, anesthesiologists-resuscitators, nurses performing invasive procedures, and staff involved in medical waste collection and transportation. Incidents most commonly occurred during surgeries, injections, and waste handling. The most frequent injury type was hand needlestick injury (81.6%), with 72.3% caused by injection needles. On average, 44.1% of incidents posed a moderate risk of HIV or viral hepatitis transmission, and 9.2% carried a high risk. Post-exposure antiretroviral prophylaxis for HIV was provided to 91.0% of those who required it. Of the healthcare workers, those at the highest risk of contracting blood-borne infections were surgeons and traumatologists, obstetricians and gynecologists, anesthesiologists and resuscitators, nurses performing invasive procedures, and employees involved in the collection and transportation of medical waste. Emergencies most often occurred during surgical interventions, injections, and when working with medical waste. By the nature of the traumatic factor, hand pricks were predominant (81.6%), including 72.3% with injection needles. On average, 44.1% of emergency situations were associated with a moderate risk of HIV and viral hepatitis infection, and 9.2% with a high risk. Coverage of post-exposure antiretroviral therapy for HIV infection among all employees who needed it was 91.0%. Conclusion. The analysis of blood exposure incidents is a critical tool for monitoring and managing occupational risks of bloodborne infections among healthcare workers. A comprehensive, multifaceted strategy is required to reduce the risk of injuries and infections.